2023
DOI: 10.3390/su151713025
|View full text |Cite
|
Sign up to set email alerts
|

European Union 2030 Carbon Emission Target: The Case of Turkey

Mehmet Kayakuş,
Mustafa Terzioğlu,
Dilşad Erdoğan
et al.

Abstract: Climate awareness caused by the threat of global warming is the number one agenda item for developed and developing economies. Plans developed in this context, environmentally friendly trends in economic activities, and countries’ efforts to adapt to sustainable development have enabled new road maps. The most important of these efforts is the Paris Climate Agreement signed in 2015 and the Green Deal implemented by the European Union (EU) within the framework of this agreement. In this study, the carbon emissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…The same or similar position in individual rankings is occupied by: Sweden (Temporal PROSA: 1, DARIA-TOPSIS: 1), Denmark (3,3), Austria (4, 5), Latvia (5, 7), Croatia (8,11), Hungary (14,14), Slovakia (16,18), Germany (20,19), Cyprus (27,25). In turn, the largest differences in terms of positions in the rankings occur in the following countries: Estonia (17, 4), Ireland (19,6), Spain (9, 23), Italy (7,21), Luxembourg (26,10), The Netherlands (23,13), Poland (25,12), Portugal (2,24), Romania (10,22). It can be concluded that for some countries the differences in rankings are significant.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The same or similar position in individual rankings is occupied by: Sweden (Temporal PROSA: 1, DARIA-TOPSIS: 1), Denmark (3,3), Austria (4, 5), Latvia (5, 7), Croatia (8,11), Hungary (14,14), Slovakia (16,18), Germany (20,19), Cyprus (27,25). In turn, the largest differences in terms of positions in the rankings occur in the following countries: Estonia (17, 4), Ireland (19,6), Spain (9, 23), Italy (7,21), Luxembourg (26,10), The Netherlands (23,13), Poland (25,12), Portugal (2,24), Romania (10,22). It can be concluded that for some countries the differences in rankings are significant.…”
Section: Discussionmentioning
confidence: 92%
“…Of particular importance in the EU in the context of energy transformation and the transition to the use of RES is the "Green Deal" program adopted in 2019. It assumes that the EU economy will become "zero-emission" by 2050 and gain energy independence [19]. Moreover, in 2021, the EU adopted the "Fit for 55" package requiring member countries to reduce greenhouse gas emissions by 55% by 2030 and assuming further increases in the use of RES [12].…”
Section: Introductionmentioning
confidence: 99%
“…In this algorithm, the data is analysed and focuses on finding a relationship between them. Unsupervised machine learning has a system structure that focuses on data [15,16].…”
Section: Machine Learning Techniquesmentioning
confidence: 99%
“…The 'Green Deal' (adopted by the EU in 2019) and 'Fit for 55' (adopted in 2021) programs are of particular importance in this respect. The first one is a plan to achieve 'zero-emissions' and energy independence by the EU economy by 2050 [1]. In turn, the second program requires EU countries to reduce greenhouse gas emissions by 55% by 2030 [2].…”
Section: Introductionmentioning
confidence: 99%